Anti-blastocystis activity of hop extracts in vitro - S.I. Pokhil; V.V. Kazmirchuk; O.M. Tymchenko; V.Y. Yevsiukova; A.L. Melnyk (Medičnì Perspektivi)
Blastocystis sp. are the most common, unicellular, anaerobic parasites of the intestinal tract of many animal and human species that can cause various digestive diseases. Metronidazole has long been used as a first-line treatment for blastocystosis, but recent clinical and in vitro studies have demonstrated its low efficacy against Blastocystis sp. The aim of this study was to determine the in vitro sensitivity of Blastocystis sp. clinical isolates to carbonic acid hop extracts and alcohol hop extracts in comparison with metronidazole. Five cultures of Blastocystis sp. were isolated from faecal samples from patients with irritable bowel syndrome with predominant diarrhoea (IBS-D, Rome IV). The parasites were identified by microscopy of faecal smears permanently stained with trichrome, Wheatley’s modification and Heidenhain’s iron-haematoxylin. Blastocystis sp. was cultivated at 37°C under anaerobic conditions on RPMI-1640 with antibiotics and horse serum, taking into account their growth characteristics. To detect the antiblastocystic activity hop extracts and metronidazole were tested in the range from 1000 μg/ml to 1 μg/ml.The presence and number of viable Blastocystis sp. cells were determined after 24, 48, 72 and 96 hours. Blastocystis sp. cells were counted in a hemocytometer using the trypan blue dye exclusion test. All experiments were performed in triplicate. According to the results of in vitro sensitivity of 5 clinical isolates of Blastocystis sp. to the action of carbonic acid hop extract, alcohoicl hop extract and metronidazole, a direct positive pattern in the dose-response and contact time-response effects was established. Alcoholic hop extract showed the highest level of antiblastocystic activity with indicators (for 72-hour parasite cultures) of the minimum inhibitory concentration (which inhibits the parasite cultures growth by 50%) (2.8±0,8) μg/ml and the minimum lethal concentration (which destroys parasite cells by 100%) – 8 μg/ml, being 2.4 and 4.5 times lower than the minimum inhibitory concentration and 8 and 62.5 times lower, than the minimum lethal concentration for hop extract and metronidazole, respectively (p<0.05). It has been shown that alcoholic hop extract (≥16 μg/ml) causes gradual morphological changes in Blastocystis sp. cells, leading to their complete destruction.In contrast to metronidazole, subinhibitory concentrations of hop extract (<2 μg/ml) do not stimulate the proliferation of Blastocystis sp. cells in vitro.